Foreigners living in Tuscany at the time of coronavirus outbreak - Caterina Silvestri; Francesco Profili; Simone Bartolacci; Fabio Voller; Cristina Stasi (Elsevier, 2023)
Background: During the coronavirus outbreak, a worldwide state of emergency and lockdown significantly affected the volunteer services for foreigners. The SARS-CoV-2 surveillance program was strengthened among migrants arriving in Italy. However, few screening measures for SARS-CoV2 infection have been conducted on the foreign population already present in Italy. In Tuscany, a great effort was made to know the epidemiological features of coronavirus outbreaks in the foreigners. Based on these premises, this study describes the prevalence and characteristics of SARS-CoV-2 infection in foreigners present in the Tuscan territory during the months of the highest incidence of this pandemic. Methods: Ministry of Health established the COVID-19 surveillance and predisposed the methods for reporting cases of SARS-CoV-2 infection in agreement with the Department of Infectious Diseases of the Istituto Superiore di Sanità. Data on SARS-CoV-2, updated daily, were collected based on the platform of the Istituto Superiore di Sanità.For each patient were available data on diagnosis, gender, age, nationality, exposure place, hospitalization and symptoms severity. Symptoms severity was classified using a 6-level scale (asymptomatic, paucisymptomatic, mild symptoms, severe symptoms, critic, and died). Results: By July 14, 2020, 10,090 SARS-CoV-2 cases were recorded. Out of 10,090 cases, 8,947 were Italians (88.7%), 608 foreigners (6%); in 535 patients (5.3%) citizenship was missing. The average age of foreigners was 44.1 years (range: 42.9-45.4), compared to 61.1 years (range: 60.7-61.5) of Italians. Chronic pathologies affected 16.8% of foreigners (14.0% -20.0%) and 36.4% of Italians (35.4% -37.4%). Foreigners with asymptomatic or mild symptoms of COVID-19 were 81.7% (78.4% -84.6%), while the Italians were 67% (66.6% -68.5%). Foreigners with severe COVID-19 were 15.2% (12.6% -18.4%) and Italians were 17.6% (16.8% -18.4%). Foreigners in critical conditions were 1.0% (0.5% -2.2%) and Italians were 2.6% (2.3% -3.0%). 38.6% (33.7% -43.7%) of foreigners were infected at the workplace as a health or social-health worker, compared to 24.2% (23.1% -25.4%) of Italians. Conclusion: The time between the onset of symptoms and the execution of the laboratory tests was similar between foreigners and Italians. The foreigners infected by SARS-COV-2 were younger compared to the Italians. Foreigners showed few comorbidities, and asymptomatic or mild symptomatic COVID-19, and consequently, a low lethality index. National and Tuscany policy decisions are needed to create equity in the access to the health care system for immigrants and their families, regardless of their immigration status.